2013 IEEE 21st International Symposium on Modelling, Analysis and Simulation of Computer and Telecommunication Systems 2013
DOI: 10.1109/mascots.2013.76
|View full text |Cite
|
Sign up to set email alerts
|

On Modeling Low-Power Wireless Protocols Based on Synchronous Packet Transmissions

Abstract: Abstract-Mathematical models play a pivotal role in understanding and designing advanced low-power wireless systems. However, the distributed and uncoordinated operation of traditional multi-hop low-power wireless protocols greatly complicates their accurate modeling. This is mainly because these protocols build and maintain substantial network state to cope with the dynamics of low-power wireless links. Recent protocols depart from this design by leveraging synchronous transmissions (ST), whereby multiple nod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…Experiments on several large-scale testbeds show that the approach is highly adaptive and achieves an end-to-end packet reliability higher than 99.9 % [19], [20]. Furthermore, the few packet losses can be considered statistically independent [28], which eases the design of CPS controllers that can deal with intermittent observations [29]. Although our approach can be adapted to other types of communication protocols, the paper is based on this concept of synchronous transmissions.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments on several large-scale testbeds show that the approach is highly adaptive and achieves an end-to-end packet reliability higher than 99.9 % [19], [20]. Furthermore, the few packet losses can be considered statistically independent [28], which eases the design of CPS controllers that can deal with intermittent observations [29]. Although our approach can be adapted to other types of communication protocols, the paper is based on this concept of synchronous transmissions.…”
Section: Related Workmentioning
confidence: 99%
“…We found that the Bernoulli assumption is highly valid to ST and significantly more valid to ST than to LT, based on the following methodology (see [10] for more details). Methodology.…”
Section: Methodology and Resultsmentioning
confidence: 99%
“…Recent protocols use synchronous transmissions (ST): multiple nodes send simultaneously towards the same receiver, as opposed to pairwise link-based transmissions (LT). ST enable efficient multi-hop protocols with little network state.We studied whether ST in Glossy enable simple yet accurate protocol modeling [10]. Based on extensive testbed experiments and statistical analyses, we found that: (i) unlike LT, packet receptions and losses with ST largely adhere to a sequence of independent and identically distributed (i.i.d.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While Marco Zimmerling et al have shown in [34] that it is largely valid to assume packet receptions under synchronous transmissions to be independent, their experiments are limited to Channel 26. As P 3 is a multi-channel system and one of its central requirements is that the independence must be true on at least four different channels, we carryout experiments to demonstrate that this requirement can be satisfied in practice.…”
Section: Channel Quality and Reception Correlation Measurementsmentioning
confidence: 99%